An intracrine view of sex steroids, immunity, and metabolic regulation - Katya B. Rubinow (Elsevier, 2018)
Background: Over the past two decades, parallel recognition has grown of the importance of both sex steroids and immune activity in metabolic regulation. More recently, these discrete areas have been integrated in studies examining the metabolic effects of sex steroid immunomodulation. Implicit in these studies has been a traditional, endocrine model of sex steroid delivery from the gonads to target cells, including immune cells. Thus, research to date has focused on the metabolic effects of sex steroid receptor signaling in immune cells. This endocrine model, however, overlooks the extensive capacity of immune cells to generate and metabolize sex steroids, enabling the production of sex steroids for intracrine signaling - that is, sex steroid production for signaling within the cell of origin. Intracrine function allows highly cell-autonomous regulation of sex steroid exposure, and sex steroid secretion by immune cells could confer paracrine signaling effects in neighboring cells within metabolic tissues. In this review, immune cell intracrinology will denote sex steroid production within immune cells for either intracrine or paracrine signaling. This intracrine capacity of immune cells has been well established, and prior work has supported its importance in autoimmune disorders, trauma, and cancer. The potential relevance of immune cell intracrine function to the regulation of energy balance, body weight, body composition, and insulin sensitivity has yet to be explored. Scope of review: The following review will detail findings to date regarding the steroidogenic and steroid metabolizing capacity of immune cells, the regulation of immune cell intracrine function, and the biological effects of immune-derived sex steroids, including the clinical relevance of immune cell intracrinology in fields other than metabolism. These findings will serve as the basis for a proposed model of immune cell intracrinology constituting a new frontier in metabolism research. Major conclusions: The development of highly sensitive mass spectrometric methods for sex steroid measurement and quantitation of metabolic flux now allows unprecedented ability to interrogate sex steroid production, metabolism and secretion by immune cells. Immune cell intracrinology could reveal key mechanisms underlying immune cell-mediated metabolic regulation. Keywords: Macrophages, Lymphocytes, Estrogens, Androgens, Intracrine, Metabolism